Education: 6. The Influence of Cultural Diversity on Openearedness - Iușcă Dorina Geta (Sciendo, 2018)
Open-earedness theory has repeatedly been confirmed on several populations including American, English, Dutch, German and Finnish people. Nonetheless the influence of cultural diversity on openness towards unfamiliar music has received little attention from researchers and this may create the possibility of adding essential modifications of Albert LeBlanc's theory. Considering the contemporary context, people's migration towards economic developed countries becomes a phenomenon with great implications related to the progress of social and cultural characteristics of any national context. Researching the openearedness of people which have been exposed not only to their native culture but also to the adopted one (due to financial necessities) may reveal a series of useful aspects for the intercultural field (by disclosing new ways to promote the tolerance towards cultural diversity) and also for the educational field (by describing new strategies of learning in a context of adaptation to an unfamiliar musical space). The present article analyses a series of previous experiments that monitored the way different social categories integrated in cultural communities different from their own assimilate or not the elements of the adopted country into their musical identity. The present analysis has educational implications related to the ways students may develop the preference for unfamiliar music.